2019
DOI: 10.1115/1.4042699
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoplasticity and Dynamic Interfacial Tension Relaxation Effects on Nucleate Pool Boiling in Aqueous Polymeric Liquids

Abstract: Nucleate pool boiling heat transfer and its ebullient dynamics in polymeric solutions at atmospheric pressure saturated conditions are experimentally investigated. Three grades of hydroxyethyl cellulose (HEC) are used, which have intrinsic viscosity in the range 5.29 ≤ [η] ≤ 10.31 [dl/g]. Their aqueous solutions in different concentrations, with zero-shear viscosity in the range 0.0021 ≤ η0 ≤ 0.0118 [N⋅s/m2], exhibit shear-thinning rheology in varying degrees, as well as gas–liquid interfacial tension relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We note that there is a large amount of literature on the effect of water-soluble polymers as additives on pool boiling [33][34][35][36][37] . Athavale et al 34 showed that the high viscous drag at the dynamic vapor-liquid interface tends to suppress or retard the post-nucleation growth of vapor bubbles, which is detrimental to the pool boiling process.…”
Section: Introductionmentioning
confidence: 99%
“…We note that there is a large amount of literature on the effect of water-soluble polymers as additives on pool boiling [33][34][35][36][37] . Athavale et al 34 showed that the high viscous drag at the dynamic vapor-liquid interface tends to suppress or retard the post-nucleation growth of vapor bubbles, which is detrimental to the pool boiling process.…”
Section: Introductionmentioning
confidence: 99%